THE REACTION OF THE NATIONAL ECONOMY FOR THE OPENING OF FOREIGN LABOR (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article presentsa theoretical concept and the study of reaction to the opening of the national economy an attractive marketfor foreign labor. The result isa theoretical reaction scheme for the opening of the national economy an attractive market for foreign labor. The result of empirical research to verify the assumptions scheme. Research on the polish economy in the years 2004-2010, and may 1, 2004 opening of labor markets in england and ireland. An important part of the considerations is the forecast for the coming year.
Keywords: migration, economy, labor market, the exchange rate